Visual Ethnography and Education: A Teaching Proposal - Κακάμπουρα, Ρέα; Κασσαβέτη, Ορσαλία-Ελένη; Σαμαρτζή, Έλλη; Μπαμπάλης, Θωμάς (Education Sciences, 2018)
Audiovisual recordings (i.e. photography, film, and video) within the context of ethnographic fieldwork, combined with the potential of New Technologies and the Internet, constitute a valuable material for the researchers as well as for the educators. Through the project method, Visual Ethnography can be applied in Education, aiming at the students’ acquaintance with their folk and popular culture and its dimensions, as well as their familiarity with audiovisual exhibits and their visual literacy. This article presents a teaching proposal, based on the project method, for the application of audiovisual ethnographic data of folk and popular culture in the Primary Education.